A philosophical reflection on the "Leuven Scale" and young children's expressions of involvement. Issue 2 (7th February 2023) - MacRae, Christina; Jones, Liz
Abstract: This paper explores the term involvement in relation to children's experiences within early years pedagogy, where it is used as a marker of a quality learning environment. We explore how philosophical enquiry offers ways of thinking more deeply about involvement as a vital quality, and how this prompts us to move beyond universal and progressive child development theories. Our discussion is grounded in the widely used Leuven Scale developed by Ferre Laevers, which we view through the prism of two data examples. The ensuing examination of both data and the scale open an appraisal of the genealogical influences underpinning the scale as well as an opportunity for us to re-read the scale through the vector of Deleuzian philosophy. The paper concludes by speculating what the repercussions might be when philosophy plays a more productive and forceful place within the context of early years education.